Analysis of a highly birefringent asymmetric photonic crystal fibre based on a surface plasmon resonance sensor. Issue 12 (3rd July 2016) - Liu, Chao; Wang, Famei; Zheng, Shijie; Sun, Tao; Lv, Jingwei; Liu, Qiang; Yang, Lin; Mu, Haiwei; Chu, Paul K.
Abstract: A highly birefringent photonic crystal fibre is proposed and characterized based on a surface plasmon resonance sensor. The birefringence of the sensor is numerically analyzed by the finite-element method. In the numerical simulation, the resonance wavelength can be directly positioned at this birefringence abrupt change point and the depth of the abrupt change of birefringence reflects the intensity of excited surface plasmon. Consequently, the novel approach can accurately locate the resonance peak of the system without analyzing the loss spectrum. Simulated average sensitivity is as high as 1131 nm/RIU, corresponding to a resolution of 1 × 10 −4 RIU in this sensor. Therefore, results obtained via the approach not only show polarization independence and less noble metal consumption, but also reveal better performance in terms of accuracy and computation efficiency.